2015
DOI: 10.1590/1678-457x.6673
|View full text |Cite
|
Sign up to set email alerts
|

Huitlacoche yield in some maize varieties in the Mediterranean region of Turkey

Abstract: Huitlacoche is the Aztecs name given to the smut galls on ears of maize caused by the pathogenic plant fungus Ustilago maydis [(DC) Corda.)]. It is known as maize mushroom, and it has been considered a delicacy and in Mesoamerica. The aim of the present study was to determine the responses of some maize varieties to the growth of the fungus in order to evaluate the prospect production of these smutty ears as a maize mushroom. A 2-year study was conducted in the Mediterranean region of Turkey in 2010 and 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…However, it was found that flint and dent corn cultivars were more suitable for huitlacoche yield than the popcorn and sweet corn varieties (Aydoğdu, 2015). Likewise, it was reported that maximum yields of huitlacoche from male-sterile field corn hybrids were about 40% greater than those from sweet corn hybrids (Pataky & Chandler, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that flint and dent corn cultivars were more suitable for huitlacoche yield than the popcorn and sweet corn varieties (Aydoğdu, 2015). Likewise, it was reported that maximum yields of huitlacoche from male-sterile field corn hybrids were about 40% greater than those from sweet corn hybrids (Pataky & Chandler, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…6.1.3 İnokulasyon: Mısır rastık hastalığı konusunda çalışan çeşitli araştırıcılar çeşitli inokulasyon teknikleri denemişlerdir. Sonuçta, ipek kanalı inokulasyon metodunun (U. maydissporidia ve teliosporlarının enjektörle mısır koçanlarının ipeklerine verilmesi) gerek rastık hastalığına karşı mısır genotiplerinin test edilmesi ve gerekse huitlacoche' nin ticari olarak üretilmesi için en uygun teknik olduğu belirlenmiştir (duToit ve Pataky 1999a; Pataky ve Chandler, 2003;Aydoğdu, 2015).…”
Section: Huitlacoche üRetimiunclassified
“…Bu yönteme göre mısır bitkileri ipek (koçan püskülü) oluşumundan sonra (bitki tozlaşması gerçek-leşmeden önce, ipekler yeşil iken) her bir bitkiye 3x106 sporidia/ml + 1x106 klamidiospor/ml yoğunluğunda 3 ml inokulum enjektörle her bitkinin koçan ipeklerine verilir (Pataky ve ark., 1995;Aydoğdu, 2015).…”
Section: Huitlacoche üRetimiunclassified
See 2 more Smart Citations